Design, synthesis, and evaluation of transition-state analogs as inhibitors of the bacterial quorum sensing autoinducer synthase CepI. (1st May 2021) - Higgins, Erin L.; Kellner-Rogers, Julian S.; Estanislau, Alexandra M.; Esposito, Alec C.; Vail, Nora R.; Payne, Sterling R.; Stockwell, Julia G.; Ulrich, Scott M.
Graphical abstract: Abstract: Quorum sensing is a bacterial signaling system that involves the synthesis, secretion and detection of signal molecules called autoinducers. The main autoinducer in Gram-negative bacteria are acylated homoserine lactones, produced by the LuxI family of autoinducer synthases and detected by the LuxR family of autoinducer receptors. Quorum sensing allows for changes in gene expression and bacterial behaviors in a coordinated, cell density dependent manner. Quorum sensing controls the expression of virulence factors in some human pathogens, making quorum sensing an antibacterial drug target. Here we describe the design and synthesis of transition-state analogs of the autoinducer synthase enzymatic reaction and the evaluation of these compounds as inhibitors of the synthase CepI. One such compound potently inhibits CepI and constitutes a new type of inhibitor against this underdeveloped antibacterial target.